Magnetic resonance imaging of pulmonary arterial compliance after pulmonary endarterectomy. Issue 5 (7th May 2020) - Ghio, Stefano; Crimi, Gabriele; Guida, Stefania; Valentini, Adele; Celentano, Anna; Pin, Maurizio; Raineri, Claudia; Turco, Annalisa; Scelsi, Laura; Oltrona Visconti, Luigi; Naeije, Robert; D'Armini, Andrea Maria
Pulmonary endarterectomy (PEA) is the treatment of choice of chronic thromboembolic pulmonary hypertension (CTEPH) [1]. However, successfully operated patients may continue to suffer from dyspnoea and limitation of exercise capacity, despite improvement or even normalisation of pulmonary artery pressure (PAP), cardiac output (CO) and pulmonary vascular resistance (PVR) [2]. This absence of complete symptomatic recovery has been explained by a decreased right ventricular (RV) function reserve due to persistent increased afterload [3, 4], related to decreased pulmonary arterial compliance (PCa) more than to mildly increased PVR [5, 6]. There is therefore interest in assessing PCa in patients during the follow-up of PEA. In CTEPH patients who have undergone pulmonary endarterectomy, exercise capacity is better associated with changes in invasively measured pulmonary arterial compliance than with changes in magnetic resonance imaging of pulmonary artery stiffness http://bit.ly/30DAWUj